TANGGUNGJAWAB KORPORASI DALAM PERKARA TINDAK PIDANA PERPAJAKAN : (Analisis Terhadap Putusan Pidana Nomor 334/PID.SUS/2020/PN.JKT.BRT) - Mohamad Sofyan Iskandar Alam (2022)
Criminal sanctions for corporations are generally not in the form of a single sanction. In addition to fines, confiscation, as well as various prohibitions for corporations are sanctions that are considered effective. Sanctions of prohibition in its various forms can be referred to as corporate imprisonment. In addition, additional sanctions in the form of announcements of judges' decisions can increase the coercive power to prevent criminal acts from being committed by corporations, but in practice, tax cases often do not involve corporations as legal subjects and criminal liability only to management or agents is considered sufficient. in the tax case Number: 292/PID.SUS/2019/PN.JKT.BRT and the tax case Number: 62/PID.SUS/2019/PN.YYK, where in that case, criminal responsibility is charged to the management or agent while the corporation is not be asked for criminal responsibility, and contrary to the Aggregation Theory where the activities of a corporation which is the output of the joint efforts of some administrators or agencies so that those who are fully responsible for these activities are the responsibility of the corporation and also to the Identification Theory (direct corporate criminal liability). According to this theory, corporation can commit a number of delicts directly through agencies who are closely related to the corporation, acting for and on behalf of the corporation. In accordance with the purpose of punishment and the deterrent effect theory, corporations can be held criminally responsible for tax crimes committed by corporations together with management or agents so that criminals will no longer repeat their crimes (deterrence effect) and against corporations who are asked to be held criminally responsible in addition to applying fines, against the corporation may be subject to additional penalties in the form of revocation of business licenses and dissolution of the company and it is hoped that law enforcement officers who handle tax cases will make a legal breakthrough to optimize criminal liability for corporations and their management in order to increase state revenue from the tax sector and make updates to the KUP Law to regulate firmly against legal subjects by imposing criminal responsibility on management and corporations.